Effectiveness Of Demonstration On Knowledge And Practice Regarding Swaddle Bath Of New Born Among Mothers Admitted In Postnatal Care Ward Of Selected Hospitals Of The City: A Pre - Experimental Study (Journal of Pharmaceutical Negative Results, 2022)
Introduction: As part of the swaddle bath method, the neonate is lightly swaddled in a towel and placed in a water tub that has been filled up to the shoulder level. The baby and the blanket are then submerged, and the individual limbs are unwrapped, washed, rinsed, and rewrapped. Therefore, this study was conducted to assess the effect of demonstration among mothers admitted to the PNC wards' on knowledge and practice of swaddling neonates.Methodology: In specific hospitals of the city, a pre-experimental one group pre- and post-test research design with a methodology of quantitative research was used among postnatal mothers admitted in PNC ward using non-probability purposive sampling technique consisting of 60 samples.Results: Analysis showed that post-test mean knowledge score and practice score demonstrated appreciable increments. Also, positive correlation was found between knowledge and practice score of mothers regarding swaddle bath of new-born and the calculated „t‟ value for knowledge and practice i.e. 48.52 and 29.84 respectively showed demonstration on knowledge and practice among mothers regarding Swaddle Bath of New Born was effective.Conclusion: The study concludes association of knowledge and practice score with age, type of family, number of children and in addition practice score with education. Therefore, it may be inferred statistically that demonstrations of knowledge and practice among mothers about swaddling newborns was effective.